Avaliação de desempenho de blocos pré-moldados de material alcalinamente ativado aplicado ao telhado verde - Arnaud, Bárbara K. Lacerda (2018)
The Civil Construction is one of the areas that have the most nonrenewable natural resources in the world, considering what is one of the pillars of the development of a society. Through the creation of new technologies, they have increasingly sought the use of less aggressive building materials with less energy use in their manufacturing process and low environmental impact. This study, this approach to sustainability in the civil building bringing together techniques of the Green Roof (TV) along with application of the Alkaline Activated Material (MAA) from the preparation of a pre-molded block for green roofs. It was evaluated the constructive pattern to be used in the preparation of the MAA mortar blocks, the type of raw material used for alkaline activation (metacaulinite and weathered soil), two types of alkaline activators (sodium and potassium silicate), two different synthesis temperatures (50 oC and 75 oC) and two different ages (1 and 7 days). The samples were characterized physically, chemically, mineralogically and microstructurally, as well as their mechanical properties in terms of compression and flexural strength. It was observed that, for the products obtained, the age and the synthesis temperature influence its mechanical properties and that the material synthesized on the basis of metacaulinite and sodium silicate at 50 oC presents better conditions for the production of blocks to be applied in green roof.